Union divided : Black musicians' fight for labor equality - Miller, Leta E. (University of Illinois Press, 2023)
"In the 1910s and 1920s, Black musicians organized more than fifty locals within the American Federation of Musicians (AFM). Leta Miller follows the AFM's Black locals from their origins and successes in the 1920s through Depression-era challenges and the postwar dismantling of segregated AFM organizations. As Miller shows, the decision by whites to organize along racial lines was hidden behind factors like genre-based audition requirements and varying approaches to musical creation. Like any union, Black AFM locals sought to ensure employment and competitive wages for members with always-evolving approaches and solutions to problems. Miller's account of these efforts includes the voices of the musicians themselves and interviews with former union members who took part in the difficult integration of Black and white locals. She also analyzes the fundamental question of how musicians benefitted from membership in the AFM. Broad in scope and rich in detail, Union Divided illuminates the complex working world of unionized Black musicians and the AFM's journey to racial inclusion"-- Provided by publisher.
Keywords: American Federation of Musicians -- History.; American Federation of Musicians; Musicians -- Labor unions -- United States.; Musicians, Black -- Labor unions -- United States.; Discrimination in the music trade.; Musiciens -- Syndicats -- États-Unis.; Musiciens noirs -- Syndicats -- États-Unis.; MUSIC / General; Musicians -- Labor unions; United States; History